Trauma and nontrauma damage-control laparotomy: The difference is delirium (data from the Eastern Association for the Surgery of Trauma SLEEP-TIME multicenter trial). Issue 1 (July 2021) - McArthur, Kaitlin; Krause, Cassandra; Kwon, Eugenia; Luo-Owen, Xian; Cochran-Yu, Meghan; Swentek, Lourdes; Burruss, Sigrid; Turay, David; Krasnoff, Chloe; Grigorian, Areg; Nahmias, Jeffry; Butt, Ahsan; et al.
Abstract : BACKGROUND: Damage-control laparotomy (DCL) has been used for traumatic and nontraumatic indications. We studied factors associated with delirium and outcome in this population. METHODS: We reviewed DCL patients at 15 centers for 2 years, including demographics, Charlson Comorbidity Index (CCI), diagnosis, operations, and outcomes. We compared 30-day mortality; renal failure requiring dialysis; number of takebacks; hospital, ventilator, and intensive care unit (ICU) days; and delirium-free and coma-free proportion of the first 30 ICU days (DF/CF-ICU-30) between trauma (T) and nontrauma (NT) patients. We performed linear regression for DF/CF-ICU-30, including age, sex, CCI, achievement of primary fascial closure (PFC), small and large bowel resection, bowel discontinuity, abdominal vascular procedures, and trauma as covariates. We performed one-way analysis of variance for DF/CF-ICU-30 against traumatic brain injury severity as measured by Abbreviated Injury Scale for the head. RESULTS: Among 554 DCL patients (25.8% NT), NT patients were older (58.9 ± 15.8 vs. 39.7 ± 17.0 years, p < 0.001), more female (45.5% vs. 22.1%, p < 0.001), and had higher CCI (4.7 ± 3.3 vs. 1.1 ± 2.2, p < 0.001). The number of takebacks (1.7 ± 2.6 vs. 1.5 ± 1.2), time to first takeback (32.0 hours), duration of bowel discontinuity (47.0 hours), and time to PFC were similar (63.2 hours, achieved in 73.5%). Nontrauma and T patients had similar ventilator, ICU, and hospital days and mortality (31.0% NT, 29.8% T). Nontrauma patients had higher rates of renal failure requiring dialysis (36.6% vs. 14.1%, p < 0.001) and postoperative abdominal sepsis (40.1% vs. 17.1%, p < 0.001). Trauma and NT patients had similar number of hours of sedative (89.9 vs. 65.5 hours, p = 0.064) and opioid infusions (106.9 vs. 96.7 hours, p = 0.514), but T had lower DF/CF-ICU-30 (51.1% vs. 73.7%, p = 0.029), indicating more delirium. Linear regression analysis indicated that T was associated with a 32.1% decrease (95% CI, 14.6%–49.5%; p < 0.001) in DF/CF-ICU-30, while achieving PFC was associated with a 25.1% increase (95% CI, 10.2%–40.1%; p = 0.001) in DF/CFICU-30. Increasing Abbreviated Injury Scale for the head was associated with decreased DF/CF-ICU-30 by analysis of variance ( p < 0.001). CONCLUSION: Nontrauma patients had higher incidence of postoperative abdominal sepsis and need for dialysis, while T was independently associated with increased delirium, perhaps because of traumatic brain injury. LEVEL OF EVIDENCE: Therapeutic study, level IV.